Forecasting euro area inflation: Does aggregating forecasts by HICP component improve forecast accuracy? - Kirstin Hubrich (European Central Bank (ECB), 2003)
Monitoring and forecasting price developments in the euro area is essential in the light of the second pillar of the ECB's monetary policy strategy. This study analyses whether the forecasting accuracy of forecasting aggregate euro area inflation can be improved by aggregating forecasts of subindices of the Harmonized Index of Consumer Prices (HICP) as opposed to forecasting the aggregate HICP directly. The analysis includes univariate and multivariate linear time series models and distinguishes between different forecast horizons, HICP components and inflation measures. Various model selection procedures are employed to select models for the aggregate and the disaggregate components. The results indicate that aggregating forecasts by component does not necessarily help forecast year-on-year inflation twelve months ahead.
Keywords: E31; E37; C53; C32; 330; Euro Area Inflation; HICP subindex forecast aggregation; linear time series models